1998
DOI: 10.1029/98jd00529
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic structure and entrainment of stratocumulus over the Southern Ocean

Abstract: The boundary layer is mostly buoyancy-driven, with shear-generated turbulence at most only half of the buoyancy-generated turbulence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The most common estimate for mid-latitude MBL entrainment for clear and cloudy conditions, however, is 3Á4 mm s (1 (e.g. Kritz, 1983;Ayers and Galbally, 1995;Boers et al, 1998;Stevens et al, 2003;Sandu et al, 2009). In most cases, the uncertainty associated with these estimates is of the order of 25Á60%.…”
Section: Entrainment Velocitymentioning
confidence: 97%
See 1 more Smart Citation
“…The most common estimate for mid-latitude MBL entrainment for clear and cloudy conditions, however, is 3Á4 mm s (1 (e.g. Kritz, 1983;Ayers and Galbally, 1995;Boers et al, 1998;Stevens et al, 2003;Sandu et al, 2009). In most cases, the uncertainty associated with these estimates is of the order of 25Á60%.…”
Section: Entrainment Velocitymentioning
confidence: 97%
“…Kritz, 1983). The primary capping inversion that separates MBL processes from the free troposphere is usually found 1000Á1900 m above sea level (Ayers and Galbally, 1995;Boers et al, 1998;Russell et al, 1998;Lenschow et al, 1999). When present, cloud base usually lies between 400 and 800 m, and the overlying cloud layer is often less than 500 m thick (Russell et al, 1998;Lenschow et al, 1999).…”
Section: Entrainment Velocitymentioning
confidence: 97%
“…We suggest that the absence of this post-sunrise ozone destruction may not have been apparent in current photochemical models when compared with observations because of the underestimation of the diurnally averaged entrainment rate of air from the free troposphere into the marine boundary layer [Boers et at., 1998], which is the major source of ozone for the remote MBL.…”
Section: Discussionmentioning
confidence: 99%
“…The differences for any particular hour are not symmetrically distributed, and there is a tendency during an individual run of baseline conditions for the ozone concentration to decrease in summer, and to a lesser extent, increase in winter with increasing time from the start of the baseline conditions[Zahorowski et al, 1996]. This leads to a net negative bias in the 24 hour average difference in summer.We have looked at 10 variations on the definition of baseline and other associated statistics such as the diurnal timing of commencement of baseline and found that this sunrise ozone decrease is robust to these definitions as is the midday summer decrease, but other apparent features vary with the definitions.Diagnostic and Explanatory ModelThe inversion capped MBL is not a permanent feature over the southern ocean, but is a transient feature that persists for about two-thirds of the time breaking up and reforming on a near weekly basis with the passage of frontal systems through this region[Boers et al, 1998]. Hence, what we observe is not an equilibrium boundary layer but one constantly reforming and approaching equilibrium.…”
mentioning
confidence: 99%
“…ity probability distribution functions, not those derived from the truncated distributions. The range of values reported by Boers et al [1998], in their analysis of airborne gust probe data from marine stratocumulus clouds are in good agreement with the range of values we report in section 2.2.2. There is also consistency with the parameterizations of VanZanten et al [1999], who conducted numerical studies of turbulence in a cloud-topped boundary layer.…”
Section: Sensitivity To Vertical Velocitymentioning
confidence: 99%